Hakikat Dan Prinsip Metode Pembelajaran Pendidikan Agama Islam - Arlina Arlina; Jeni Anwar Rambe; Muhammad Zailani; Rani Wardani Hasibuan; Nadya salsabilah; Rizka Ardianti (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The method is very important in facilitating a job because the method is a systemic way of working to facilitate the implementation of an activity in order to achieve the specified goals. The Islamic Religion Learning Method itself certainly cannot be separated from the main objectives of religious education in Indonesia which are listed in article 39 paragraph 2 of Law no. 20 of 2003, "education is an effort to strengthen faith and devotion to God Almighty in accordance with the religion professed by the students concerned by taking into account the demands to respect other religions in the relationship of inter-religious harmony in society to realize national unity. This PAI learning methodology will be meaningless if it is not implemented in educational practice. The implementation of the PAI learning methodology in learning includes the selection of effective and efficient teaching methods. In the Qur'an there are many methods that can be applied to convey God's words to humans, such as the story method, discussion, question and answer (dialogue), parable method (metaphor), method of punishment and reward.